Assessing Feedback Efficacy in Classroom Assessment: The Art of Grading With a Wink and a Nod - Suhardiana, I Putu Andre (Universitas Pendidikan Ganesha, 2024)
Although higher education used a range of assessment methods, yet there remains uncertainty about how effectively feedback is provided to students. This study focused on evaluating current feedback practices in classroom assessments within the English Language Education Study Program at the university level. The study, conducted as a descriptive quantitative study, involved 87 participants selected through stratified random sampling, comprising 8 lecturers and 79 students. Data was collected using a questionnaire and analysed using SPSS software. Findings revealed that lecturers predominantly utilized class tests (62%), exercises, and homework for evaluation, with a preference for essay (87.5%) and multiple-choice formats (75%). Nevertheless, both lecturers (50%) and students (65.82%) identified challenges such as delays in returning graded tests, inefficient distribution of results, unclear explanation of errors, lack of student motivation for improvement, inadequate support for revisions, and ineffective communication of results to parents. Indeed, some lecturers provided feedback, guided students’ development, and used assessments for counseling purposes. The study concluded that although traditional assessment methods were used, there was a need for more efficient feedback practices.